Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1103/physrevlett.99.127201
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Ferromagnetism in Carbon-Doped ZnO

Abstract: We report magnetism in carbon doped ZnO. Our first-principles calculations based on density functional theory predicted that carbon substitution for oxygen in ZnO results in a magnetic moment of 1.78 µ B per carbon. The theoretical prediction was confirmed experimentally. Cdoped ZnO films deposited by pulsed laser deposition with various carbon concentrations showed ferromagnetism with Curie temperatures higher than 400 K, and the measured magnetic moment based on the content of carbide in the films (1.5 − 3.0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
245
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 793 publications
(277 citation statements)
references
References 40 publications
24
245
0
1
Order By: Relevance
“…Despite these developments, magnetic-impurity-based DMS oxides are the subject of intense debate as a result of the many inconsistent results related to secondary phase formation, unknown impurities or substitutionality, solubility, clustering and/or segregation of the magnetic impurities in the host oxide matrix [16][17][18]. More recently, there have been reports of FM in ZnO and other oxides (attributed to anionic vacancies) by doping with non-magnetic ions, but besides evidence from superconducting quantum interference device (SQUID) data [13][14][15], a necessary but not sufficient criterion [17,18], there has been no reliable element-specific evidence for FM in these cases, with the exception of recent publications [19,20]. To establish true FM in the DMS oxides and to differentiate from impurity artefacts, various magnetic measurements-ranging from extremely sensitive SQUID and optical magnetic circular dichroism (OMCD) measurements, which directly probe the spin-polarized bands, to element-specific soft X-ray magnetic circular dichroism (SXMCD) measurements-are required.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these developments, magnetic-impurity-based DMS oxides are the subject of intense debate as a result of the many inconsistent results related to secondary phase formation, unknown impurities or substitutionality, solubility, clustering and/or segregation of the magnetic impurities in the host oxide matrix [16][17][18]. More recently, there have been reports of FM in ZnO and other oxides (attributed to anionic vacancies) by doping with non-magnetic ions, but besides evidence from superconducting quantum interference device (SQUID) data [13][14][15], a necessary but not sufficient criterion [17,18], there has been no reliable element-specific evidence for FM in these cases, with the exception of recent publications [19,20]. To establish true FM in the DMS oxides and to differentiate from impurity artefacts, various magnetic measurements-ranging from extremely sensitive SQUID and optical magnetic circular dichroism (OMCD) measurements, which directly probe the spin-polarized bands, to element-specific soft X-ray magnetic circular dichroism (SXMCD) measurements-are required.…”
Section: Introductionmentioning
confidence: 99%
“…The most reproducible carrier-induced FM in semiconductors is based on Mn doping of GaAs, but its Curie temperature, T C , is limited to about 173 K [3,7]. Among the oxides, the most notable compounds exhibiting DMS behaviour above RT are based on TiO 2 and ZnO [8][9][10][11][12][13][14][15]. Despite these developments, magnetic-impurity-based DMS oxides are the subject of intense debate as a result of the many inconsistent results related to secondary phase formation, unknown impurities or substitutionality, solubility, clustering and/or segregation of the magnetic impurities in the host oxide matrix [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second case, Straumal et al have proposed the concept of specific grain boundary area and its influence/role in terms of magnetic foam model to explain RTFM in nanograined Mn doped ZnO [15]. More complexity is very recently introduced by the observation of RTFM behavior in carbon doped ZnO [16,17]. Pan et al reported RTFM in carbon doped ZnO Films deposited by pulsed laser deposition with Curie temperature higher than 400K and this ferromagnetism is due to Zn-C system in the ZnO environment [16].…”
Section: Resultsmentioning
confidence: 99%
“…[10] Experimentally, RT ferromagnetism was reported in C-doped ZnO and SnO 2 . [11,12] Theoretical studies reveal that holes in valence band play an important role in d 0 ferromagnetism. By doping impurities with weaker electronegativity or lower valence into semiconductors of oxide or nitride, holes are introduced into the valence band of semiconductors, which leads to band magnetization.…”
Section: Introductionmentioning
confidence: 99%